Distinguishing Between Invalidity and Corruption among Shafi’i Jurisprudential Scholars: An Analytical Study - Kweder, Abdullah Abdulkader; Jaber, Tariq Yousef Hasan; Kouider , Mohamad Abdulkader (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study aims to clarify how Shafi’i scholars differentiate between "corruption" and "invalidity" and whether there is consensus on this matter. The research problem revolves around determining their position and investigating if it is agreed upon or subject to disagreement. The prevalent notion that this differentiation is specific to the Hanafi school necessitates a thorough examination of Shafi’i foundational texts for validation or rejection. Methods: Adopting an analytical approach, the research analyzes Shafi’i foundational texts regarding the differentiation between corruption and invalidity. It refers to authentic works on Shafi’i jurisprudence, especially those known for meticulous scrutiny and analysis. The comparative method is employed to compare diverse opinions among Shafi’i scholars and engage in discussions. Results: The findings indicate that valid contracts or actions are categorized into two groups: those with no consequential effects, considered void, and those resulting in some effects, regarded as corrupt. Some Shafi’i scholars maintain this distinction, differing from the Hanafi school. The origin of this differentiation varies from that of the Hanafi school, necessitating a distinction between the two terms in both schools. Conclusions: The interchangeability of the terms "corruption" and "invalidity" among Shafi’i scholars lacks consensus and is subject to differences. This underscores the importance of cautious interpretation when attributing opinions to jurisprudential schools and foundational traditions.